1998
DOI: 10.2134/jeq1998.00472425002700040007x
|View full text |Cite
|
Sign up to set email alerts
|

Alachlor Dissipation in Shallow Cropland Soil

Abstract: A soil-column laboratory experiment and a 2-yr field-sampling study evaluated the overall dissipation of alachlor [2-chloro-N-(2,6-diethylphenyl)-N-(methoxymethyl) acetamide]. Theses studies also measured the effect of no-till and chisel-plow tillages on alachlor leaching and dissipation. In the top 30 cm layer of soil, the overall half-life was 3 d or less, and the time to 90% dissipation ranged from 17 to 30 d. In no-fill soil, alachlor dissipated slightly faster, and more was transported into the 10 to 30 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The predicted half-lives for the soils are in the upper range of estimated values from field experiments on surface soils (Aga and Thurman, 2001;Weed et al, 1998.). The alachlor may have been more persistent in these soils because they were saturated.…”
Section: Kinetics Of Alachlor Degradationmentioning
confidence: 76%
“…The predicted half-lives for the soils are in the upper range of estimated values from field experiments on surface soils (Aga and Thurman, 2001;Weed et al, 1998.). The alachlor may have been more persistent in these soils because they were saturated.…”
Section: Kinetics Of Alachlor Degradationmentioning
confidence: 76%
“…Alachlor and bentazone degradation usually fit a first‐order model (Weed et al, 1998; Thorstensen and Lode, 2001): C=C0exptrue(kttrue)where C is the soil concentration of parent molecule at time t (d), C 0 is the concentration at time 0, and k is the rate constant (d −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pore volume of the soil used was 57.5 mL. The percentage of herbicide eluted after the CF application was 39.4% (Figure 2b), which was less than what would be expected in a sandy soil with a low content of clay and organic matter, because alachlor adsorption is strongly correlated with both soil properties (13)(14)(15). Similar results were obtained by Johnson and Pepperman (19), who found that the herbicide amount leached from commercial and technical alachlor was approximately 33% in sandy soil columns.…”
Section: Alachlor Encapsulation In Ethylcellulose Microspheresmentioning
confidence: 89%